Lessons Learned about Teaching and Management during the COVID-19 Pandemic among Faculty of Nursing Rajabhat’s University Thailand - Buachu, Thinnakorn; Khunkaew, Saneh; ใจมาคำ, กมลทิพย์ (Journal of The Royal Thai Army Nurses, 2023)
This descriptive qualitative research aimed to extract lessons learned from teaching and learning management during the pandemic situation of the corona virus 2019 of the Rajabhat University in Thailand. The informants were three Rajabhat University Nursing Education Administrators, two Rajabhat University who responsible for the course and three Rajabhat University Nursing lecturers. A total of eight people were collected through in-depth individual interviews. Data were analyzed by thematic analysis. The results of the research found that teaching and learning management and management during the 2019 coronavirus pandemic can be classified into three main themes and six sub-themes that make teaching and learning management successful as follows: 1) teaching and learning management during the COVID-19 outbreak in sections 1.1 online teaching, 1.2 facilities and 1.3 evaluation; 2) problems/obstacles of learning management during the COVID-19 outbreak in section 2.1 teachers and 2.2 learners and 3) future instructional management guidelines in section 3.1 advantages from online learning and in the nursing laboratory before practice. Therefore, nursing institutions in Rajabhat University group should be taken into consideration in teaching and learning management in order to raise the quality of graduates to be desired by graduate users and to support the changing context of society further.